Portland Versus Alkaline Cement: Continuity or Clean Break: “A Key Decision for Global Sustainability” - Palomo, A.; Maltseva, O.; Garcia-Lodeiro, I.; Fernández-Jiménez, A. (Frontiers in Chemistry, 2021)
This review undertakes rigorous analysis of much of the copious literature available to the scientific community on the use of alkali-activated binders (AABs) in construction. The authors’ main intention is to categorically refute arguments of that part of the scientific community underestimating or even dismissing the actual potential of AABs as alternatives to Portland cement (PC). The main premise invoked in support of those arguments is a presumed lack of material resources for precursors that would make AAB industrial-scale production unfeasible anywhere on the planet (a substantial number of scientific papers show that the raw materials required for AAB manufacture are in abundance worldwide). The review also analyses the role of alkaline activators in the chemistry of AABs; it is important to clarify and highlight that alkaline activators are not, by any means, confined to the two synthetic products (caustic soda and waterglass) mostly employed by researchers; other sustainable and efficient products are widely available. Finally, the review deals with the versatility of AAB production processes. The technologies required for the large scale manufacturing of AABs are mostly already in place in PC factories; actually no huge investment is required to transform a PC plant in a AAB factory; and quality and compositional uniformity of Alkaline Cements (binders produced through an industrial process) would be guaranteed. The last conclusions extracted from this review-paper are related with: i) the low carbon footprint of one-part AABs and ii) the urgent need of exploring standardization formulas allowing the commercial development of (sustainable) binders different from PC.